Karakteristik biskuit bagiak dengan substitusi konsentrat protein ikan (KPI) dan tepung tulang ikan : Characteristics of bagiak biscuits with fish protein concentrate and fish bone flour substitution - Setyarini, Dian; Ibrahim, Bustami; Santoso, Joko (Jurnal Pengolahan Hasil Perikanan Indonesia, 2024)
Bagiak is a biscuit made of sago flour, tapioca, arrowroot starch, sugar, and other ingredients. Bagiak is high in carbohydrates, but low in proteins. The aim of this study was to determine the best formulation resulting from the substitution of catfish protein concentrate and addition of catfish bone meal in making bagiak biscuits. The study used an experimental method with a completely randomized factorial design (RALF) with two treatments, namely substitution of catfish protein concentrates (FPC) for main meal (0%, 10%, 20%, and 30%) and addition of catfish bone meal (0, 1, 2, 3 %). For the selected formulas, the hedonic test results were analyzed, including protein and calcium levels, and test parameters according to SNI Biscuits 2973:2022. The selected formula was a 10% KPI formulation and 3% fishbone meal. The selected bagiak formulation produced a protein content of 10.90±0.01% and calcium of 572.32 mg/100 g. The protein and calcium levels of the selected bagiak were greater than those of the control and commercial bagiak. Test results for selected water content parameters, total aerobic plate number, Enterobacteriaceae, Salmonella spp., Staphylococcus aureus, heavy metal contamination: Lead (Pb), Cadmium (Cd), Tin (Sn), Mercury (Hg), and (As) met the SNI Biscuit quality requirements, SNI 2973:2022. The 10% FPC formulation and 3% fish bone meal have the potential to be nutritious snacks with better protein and calcium contents than commercial products.